2004
DOI: 10.1074/jbc.m314014200
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface Expression of α1D-Adrenergic Receptors Is Controlled by Heterodimerization with α1B-Adrenergic Receptors

Abstract: ␣ 1 -Adrenergic receptors (ARs) belong to the large Class I G protein-coupled receptor superfamily and comprise three subtypes (␣ 1A , ␣ 1B , and ␣ 1D ). Previous work with heterologously expressed C-terminal green fluorescent protein (GFP)-tagged ␣ 1 -ARs showed that ␣ 1A -and ␣ 1B -ARs localize to the plasma membrane, whereas ␣ 1D -ARs accumulate intracellularly. We recently showed that ␣ 1D -and ␣ 1B -ARs form heterodimers, whereas ␣ 1D -and ␣ 1A -ARs do not. Here, we examined the role of heterodimerization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
140
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(157 citation statements)
references
References 68 publications
13
140
1
Order By: Relevance
“…Since we have demonstrated that inhibition of α 2B -AR cell-surface expression is mediated through dimerization of mutant and WT receptors, it is possible that the inhibitory effect of α 2B -ARm on the transport of α 2A -AR and α 2C -AR is also due to heterodimerization of α 2B -ARm with α 2A -AR or α 2C -AR. This possibility is supported by a number of observations demonstrating that closely related members of G protein-coupled receptors may heterodimerize [11,14,[37][38][39]. Furthermore, α 2A -AR and α 2C -AR indeed form heterodimers with β 1 -AR and M 3 -muscarinc receptor, respectively [40,41].…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Since we have demonstrated that inhibition of α 2B -AR cell-surface expression is mediated through dimerization of mutant and WT receptors, it is possible that the inhibitory effect of α 2B -ARm on the transport of α 2A -AR and α 2C -AR is also due to heterodimerization of α 2B -ARm with α 2A -AR or α 2C -AR. This possibility is supported by a number of observations demonstrating that closely related members of G protein-coupled receptors may heterodimerize [11,14,[37][38][39]. Furthermore, α 2A -AR and α 2C -AR indeed form heterodimers with β 1 -AR and M 3 -muscarinc receptor, respectively [40,41].…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, dimers are unable to export from the ER. Dimerization has been well described for a variety of G protein-coupled receptors [9][10][11][12][13][14][15][34][35][36][37][38][39][40][41]. However, whether α 2B -AR is capable of forming homodimers has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, 3-month-old KO mice had almost no hepatic a 1 -adrenoceptor binding. This would indicate that replacement of the missing a 1B adrenoceptor by the a 1A is a relatively slow process, and suggest that, in general, comparisons of receptor density between WT and KO mice should be made at multiple time points.Based on multiple literature reports, it is now clear that a 1 -adrenoceptors are not confined to the cell membrane, and that the subcellular localization can differ between subtypes (Mackenzie et al, 2000;Stanasila et al, 2003;Hague et al, 2004). Deighan et al (2004) show that the distribution of a 1A adrenoceptors in KO mice is identical to that of the a 1B in WT mice, consistent with the ability of the two subtypes to mediate the same physiological function.…”
mentioning
confidence: 94%